DEVELOPMENT OF A SOLAR WATER HEATING CONVECTIVE UNIT FOR DRYING MEDICINAL PLANTS - Sultanova, A.; Safarov, J. E. (International Journal of Psychosocial Rehabilitation, 2020)
This article outlines the approach selection dryer for drying capillary porous medicinal plants convection method in large volumes. When collecting medicinal herbs need to know where to focus the useful elements and in what period of plant development, their concentration is maximum, the most widely used medical plants in traditional medicine. Various types of drying equipment convective type. Is a schematic drawing of container-convection dryer, data components and parts. It is shown that the current state of the problem, the causes and the sound data to the chosen methodology is summarized.